Rehabilitation needs screening to identify potential beneficiaries: a scoping review - Carla Sabariego; Wouter De Groote; Melissa Corso; Kent Murnaghan; Antony Duttine (BMJ Public Health)
Objectives The aim is to identify and compare the content of screening tools and needs assessments used to select rehabilitation beneficiaries and to describe the context of their use.Design Scoping review.Data sources We systematically searched five indexed databases for studies published from 1 January 2010 to 3 February 2023.Eligibility criteria We searched for papers published in English only. Papers describe a screening tool or needs assessment aiming to prospectively select potential beneficiaries of rehabilitation services based on a cut-off score or classification system.Data extraction and synthesis We charted the evidence according to the characteristics of the paper, rehabilitation needs screening context, screening tool and content of the screening tool. A descriptive synthesis is provided for screening methodology, settings, target populations, rehabilitation need types and phases of care. The WHO International Classification of Functioning, Disability and Health is used to categorise screening items.Results We identified 24 tools that use a range of screening methodologies, but mostly questionnaires that are used by health workers. Most tools have been proposed for the identification of a rehabilitation beneficiary among people with selected health conditions assessing the need to access a specific rehabilitation intervention, programme or occupational group. The majority of tools screen for current functioning limitations, and this is often the only screening component. When mapping screening items with the WHO International Classification of Functioning, Disability and Health (ICF), almost all ICF chapters for body functions and activities and participation have been included across screening tools, with the following most frequently included ICF categories: emotional functions (b152), acquiring, keeping and terminating a job (d845), sensation of pain (b280) and carrying out daily routine (d230).Conclusions Rehabilitation need screening tools commonly include the screening for current functioning limitations among people with selected health conditions. A screening tool that is applicable across health conditions and settings is not available.